Simulação de sistemas de drenagem urbana sustentável aplicada em um loteamento urbano utilizando o EPA SWMM - Toscan Neto, Ângelo (2019)
The town of Dois Vizinhos -PR follows the regional reality and presentswide horizontal urban growth. Most are built using conventional urban drainage systems. However, this approach of urban drainagehas been changed over the years, being complemented or replaced by newer ones. Thus, new techniques such as Sustainable Urban Drainage Systems (SuDS) have emerged, which aim at controllingthe surface runoff at the source, reducing volumes and flow rates close to those before urbanization. Based on this analysis, a region-specific basinwas chosen in order to model the hydrographs of the drainage network for pre and post-occupation conditions, and to evaluate the measures of sustainable urban drainage in terms of effectiveness to reduce the runoff. The Storm Water Management Model (SWMM), developed by the Environmental Protection Agency (EPA), was used for modeling.The rainfall data were obtained by a rain gauge installed in the site and the runoff datawere obtained, through a parshall flumeinstalled in the drainagesystem outlet. Model calibration and validation was performed using experimental data. The post occupation scenario was formulated considering the guidelines of the municipal masterplan.To control the surface runoff, the adopted measures were: detention reservoir, detention basin, and infiltration trenches. When comparing the total surface flow volume of the pre-occupation scenariowith the post-occupation scenario, an increase of more than 118% was observed. The peak flow increased, from 41.83 L/s to 142.21 L/s, comparing the same previous scenarios. The implementation of infiltration trenches associated with a detention basin was able to reduce the total flow volume as well as the peak flow. On the other hand, the use of detention reservoirs was not efficient in such purposes.